2022
DOI: 10.1098/rstb.2020.0422
|View full text |Cite
|
Sign up to set email alerts
|

Forensic genetics through the lens of Lewontin: population structure, ancestry and race

Abstract: In his famous 1972 paper, Richard Lewontin used ‘classical’ protein-based markers to show that greater than 85% of human genetic diversity was contained within, rather than between, populations. At that time, these same markers also formed the basis of forensic technology aiming to identify individuals. This review describes the evolution of forensic genetic methods into DNA profiling, and how the field has accounted for the apportionment of genetic diversity in considering the weight of forensic evidence. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 72 publications
0
7
0
1
Order By: Relevance
“…AMOVA revealed that most of the variance (97.12%) in allele frequencies occurred within populations, corroborating previous studies [ 44 , 45 ]. A study that evaluated human population structure using genotypes at 377 autosomal microsatellite loci in 1056 individuals from 52 worldwide populations revealed that the variance within populations accounts for 93 to 95% of genetic variation, while differences among major groups constitute only 3 to 5% [ 45 , 46 ]. Although the number of populations and genetic markers are quite different, the larger amount of variance within populations and lower variance among groups observed in the present study may be either due to chance or to the fact that forensic STRs do show relatively lower F ST than random STRs due to the increased heterozygosity of the former [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…AMOVA revealed that most of the variance (97.12%) in allele frequencies occurred within populations, corroborating previous studies [ 44 , 45 ]. A study that evaluated human population structure using genotypes at 377 autosomal microsatellite loci in 1056 individuals from 52 worldwide populations revealed that the variance within populations accounts for 93 to 95% of genetic variation, while differences among major groups constitute only 3 to 5% [ 45 , 46 ]. Although the number of populations and genetic markers are quite different, the larger amount of variance within populations and lower variance among groups observed in the present study may be either due to chance or to the fact that forensic STRs do show relatively lower F ST than random STRs due to the increased heterozygosity of the former [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jobling [27] discusses forensic genetics, an important societal application of population-genetic ideas. Although allele-frequency differences among human populations tend to be small, Lewontin forcefully pointed out that they nonetheless introduce complications when one is trying to quantify the strength of evidence provided by a genetic match between a suspect and a crime-scene sample.…”
Section: (C) Practical Problems In Human Geneticsmentioning
confidence: 99%
“…[28,29]). As discussed by Novembre [2], Lewontin's paper [1] has been referenced beyond the field of human evolutionary genetics as supporting an oversimplified view of human variation, in which population structure is completely ignored even in situations in which it might be relevant, such as matching problems in forensics or transplantation, where population variation in match probabilities affects the societal use of population-genetic computations [27,29].…”
Section: Lewontin's 1972 Paper: a Celebrationmentioning
confidence: 99%
“…Because the typical person has many distant cousins, even a database that includes only a small fraction of the population (≈2%) will include genetically detectable cousins of the majority of the population (Erlich, Shor, Pe'er, Phenotype predictions in forensic contexts, termed forensic DNA phenotyping (FDP), have been explored in the academic literature (Walsh et al, 2013;Claes et al, 2014;Kayser, 2015;Chaitanya et al, 2018;Schneider, Prainsack, & Kayser, 2019) and are currently marketed to law enforcement (Wienroth, 2018). Forensic interest in phenotype prediction focuses on so-called externally visible traits (EVTs), which might be perceived by a witness (Jobling, 2022). Sex, predicted from sex chromosome karyotype, has been used in this way for some time (Sullivan, Mannucci, & P, 1993), notwithstanding some errors resulting from imperfect matches between sex chromosome karyotype and sex, or between sex and gender identity or presentation.…”
Section: Blair Underwoodmentioning
confidence: 99%
“…Although coarse pigmentation prediction (e.g., classifying blue vs. brown eyes, but not green vs. hazel) can be reasonably accurate for eyes, hair, and skin, at least in some groups (excluding possibilities such as dyed hair, colored contact lenses, greying of hair with age, etc. ), predictive performance on most facial traits is not accurate enough for reliable face reconstruction (Schneider et al, 2019;Jobling, 2022). For some facial phenotypes, predictive accuracy is limited in principle by moderate heritability under current conditions (Šešelj, Duren, & Sherwood, 2015;Cole et al, 2017;Tsagkrasoulis, Hysi, Spector, & Montana, 2017).…”
Section: Blair Underwoodmentioning
confidence: 99%